Examining the Role of Attention and Sensory Stimulation in the Attentional Repulsion Effect - Petersson, Anna M.; Hilchey, Matthew D.; Pratt, Jay (Frontiers in Psychology, 2019)
It has been suggested that visual attention warps space, such that stimuli appearing near its locus are perceived as farther away than they actually are. This is known as the attentional repulsion effect (ARE). Recent data challenge the role of attention as the sole factor responsible for the ARE, suggesting instead that the ARE is, at least in part, a product of low level sensory interactions between a peripheral orienting cue and the Vernier target stimulus used to measure the effect. Here, we directly test whether attentional orienting, without a cue in peripheral vision to guide attention, is sufficient for generating an ARE. In Experiment 1, attention was guided to the visual periphery by a central symbolic cue that reliably indicated the locations of to-be-identified targets in peripheral vision. On a subset of trials, we probed for an ARE with Vernier targets. Reaction time (RT) data revealed that the cue guided attention but there was no trace of an ARE. In Experiment 2, we ensured that the Vernier targets were sensitive to the ARE by using the standard spatially uninformative peripheral cue to guide attention instead of the central symbolic cue. RT data again revealed that the cue guided attention, while the Vernier targets revealed an ARE. Collectively, these data suggest that attentional orienting is not sufficient for generating an ARE.